Melatonin Improves Quality of Repeated-Poor and Frozen-Thawed Embryos in Human, a Prospective Clinical Trial - Bao, Zhongjian; Li, Guangdong; Wang, Rongxiang; Xue, Songguo; Zeng, Yong; Deng, Shoulong (Frontiers in Endocrinology, 2022)
Objective: In numerous clinics, good-quality embryos are selected for embryo transfer and cryopreservation, and poor-quality embryos are discarded. Patients with repeated-poor quality as well as inferior vitrified-warmed embryos frequently suffer from in vitro fertilization (IVF) failures. In this study, two experiments were performed to assess the effect and the role of melatonin on human in vitro embryo quality. Methods: Experiment I: A total of 42 repeated-poor-quality-embryo patients were enrolled, with a total of 181 oocytes retrieval cycles. After IVF, for the same patient, the MT cycles group (10-7 M melatonin added to the culture medium; n=48) were compared with the previous non-MT cycles group (n=133), following by in vitro culture to the blastocyst stage and embryo transfer. 31 patients were transplanted with 65 transplant cycles, including 24 MT transplant cycles, 41 non-MT transplant cycles. Cycle outcomes were compared between the two groups. Experiment II：A total of 143 supernumerary human cleavage-stage embryos (from non-repeated-poor-quality-embryo patients) vitrified on Day 3 after IVF were warmed and randomized into two groups: melatonin group (10-7 M melatonin added to the culture medium; n=71) and control group (n=72), and then cultured for 72 h. Rate of blastocyst and high-quality blastocyst, reactive oxygen species (ROS) levels of culture media as well as embryonic GPX1, CAT, Mn-SOD, Cu/Zn-SOD, BCL-2, BAX gene expression levels were analyzed. Results: Experiment I: Results showed that the rate of Day 3 high-quality embryos (29.6% vs.19.5%) in the MT cycles group was significantly higher than that in the non-MT cycles group (P<0.05). The rate of available blastocysts (17.1% vs.12.7%) and clinical pregnancy rate (25.0% vs.17.1%) were in tendency higher in the group treated with melatonin (P>0.05). Experiment II：Results showed that the blastocyst rates in the melatonin administered group were significantly higher than in control group (42.25% vs.26.38%, P<0.05). There were no significant differences in high-quality blastocyst rates. In addition, quantitative PCR showed that the expression of CAT was significantly upregulated by melatonin treatment (P<0.05), while there were no significant differences in the expression of GPX1, Mn-SOD, Cu/Zn-SOD, BAX and BCL-2 gene as well as the levels of ROS.